2023
DOI: 10.1186/s12884-023-05349-3
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in the time of COVID-19: towards Fetal monitoring 4.0

Abstract: On the outbreak of the global COVID-19 pandemic, high-risk and vulnerable groups in the population were at particular risk of severe disease progression. Pregnant women were one of these groups. The infectious disease endangered not only the physical health of pregnant women, but also their mental well-being. Improving the mental health of pregnant women and reducing their risk of an infectious disease could be achieved by using remote home monitoring solutions. These would allow the health of the mother and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 127 publications
0
8
0
Order By: Relevance
“…In terms of drug utilization, we observed that a total of 72% of pregnant women with COVID-19 received a prescription, and 66.6% among women without COVID-19. Although there have been several factors that might affect the rates of drug prescriptions during the pandemic, such as public health policies, limited or inadequate healthcare prenatal visits, change in birth plan, limited care, quarantine and mobility restrictions [ 25 , 26 , 27 , 28 ], our results are in line with prior studies conducted before the COVID-19 outbreak, where they found a wide range in prevalence of receiving at least one prescription, from 27 to 93% [ 14 ]. The most relevant therapeutic groups prescribed in our study were analgesics (especially acetaminophen), antibiotics and thyroid hormones, in line with prior studies [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of drug utilization, we observed that a total of 72% of pregnant women with COVID-19 received a prescription, and 66.6% among women without COVID-19. Although there have been several factors that might affect the rates of drug prescriptions during the pandemic, such as public health policies, limited or inadequate healthcare prenatal visits, change in birth plan, limited care, quarantine and mobility restrictions [ 25 , 26 , 27 , 28 ], our results are in line with prior studies conducted before the COVID-19 outbreak, where they found a wide range in prevalence of receiving at least one prescription, from 27 to 93% [ 14 ]. The most relevant therapeutic groups prescribed in our study were analgesics (especially acetaminophen), antibiotics and thyroid hormones, in line with prior studies [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Continuous monitoring of FHR via cardiotocography (CTG) or electronic fetal monitoring provides insight into fetal well-being. 17 Hypoxemia in the mother can compromise fetal oxygenation, affecting the FHR.…”
Section: Fetal Parameters-fetal Heart Rate (Fhr)mentioning
confidence: 99%
“…[5][6][7][8] The COVID-19 pandemic accelerated the use of RPM, digital health tools, and telemedicine across a wide variety of medical fields with potential benefits including a reduced time to diagnosis and improved access to specialist care. [8][9][10][11][12][13][14] In addition, remote technology allows for higher-frequency data collection compared to traditional in-person office visits. 13 The increased data collection has the potential to lead to more accurate predictors of pregnancy complications and provide more timely feedback to physicians and patients.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] In addition, remote technology allows for higher-frequency data collection compared to traditional in-person office visits. 13 The increased data collection has the potential to lead to more accurate predictors of pregnancy complications and provide more timely feedback to physicians and patients. 15,16 The objective of this study was to describe the prenatal care and pregnancy outcomes in patients who used the Babyscripts™ prenatal care digital health platform and identify predictors of RPM engagement and complications of pregnancy.…”
Section: Introductionmentioning
confidence: 99%